Government transfers and consumer spending among households with children during COVID-19 - Pinghui Wu; Vincent Fusaro; H. Luke Shaefer (Federal Reserve Bank of Boston, 2022)
Leveraging novel data on consumer credit and debit card spending by Zip code, this study examines how the impact of government transfers on economic well-being varied by household type during the COVID-19 pandemic. Our findings indicate that pandemic transfers disproportionately benefited households with children, buffering them from earnings losses at the pandemic's start and sustaining spending growth over time. Household essential spending increased proportionally with the delivery of cash transfers, while discretionary spending was influenced more by pandemic-specific factors beyond household income. Our results also offer preliminary evidence that households with children had a higher marginal propensity to consume during the early stages of the pandemic. These findings highlight the efficacy of government transfers in safeguarding household consumption during a period of large-scale job loss.
Keywords: H31; I31; 330; consumer spending; children; government transfers; COVID-19